Resident Competency and Proficiency in Combined Spinal-Epidural Catheter Placement is Improved Using a Computer-Enhanced Visual Learning Program: A Randomized Controlled Trial. Issue 2 (June 2020) - Nixon, H.C.; Stariha, J.; Farrer, J.; Wong, C.A.; Maisels, M.; Toledo, P.
Abstract : ( Anesth Analg . 2019;128:999–1004) The apprenticeship model is still the most common method for residents to learn the technical skill of placing a spinal-epidural catheter. However, this method has its drawbacks, as on average it takes 45 to 60 attempts for a student to achieve a 90% success rate. While other methods have also been explored to teach this skill, such as watching videos of the procedure before attempting it, this study proposed that E-learning is a valid method to enhance anesthesiology education.